Alternative Questions in Turkish - Martina Gračanin-Yüksek (Dilbilim Araştırmaları Dergisi)
The paper examines alternative questions in Turkish from the perspective of the size of the disjoint constituents. At the moment, there exists no consensus in the literature on the topic as to whether alternative questions involve clausal disjunction accompanied by a deletion operation in one or both of the disjuncts or they contain no phantom structure, i.e. are disjunctions of phrases no bigger than they appear on the surface. Both of these views have been proposed over the years: a big-disjunct analysis has been advocated by Gračanin-Yüksek (2016), Han and Romero (2004a, 2004b), and Roelofsen and Pruitt (2011) among others, while Beck and Kim (2006), Erlewine (2014), and Larson (1985) among others have defended the small-disjunct analysis. In this paper, looking at possible word order patterns of alternative questions in Turkish, I show that properties of alternative questions in this language cannot be explained on the small-disjunct analysis. I present evidence that underlyingly, alternative questions in Turkish involve clausal disjuncts. Next, by examining the distribution of the question particle in alternative questions and comparing it to the distribution of the same particle in polar questions, I propose that the disjuncts in Turkish alternative questions are full CPs.